PENGARUH PENDEKATAN CONFERENCING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KEMAMPUAN MENULIS KARANGAN NARASI SISWA KELAS V SEKOLAH DASAR NEGERI 26 ARUNGKEKE KABUPATEN JENEPONTO - Mila Karmila; Munirah Munirah; Tarman A. Arief (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to determine the students’ ability to write narrative essays and to determine the significant effect of conferencing approach assisted by audio-visual media for grade Vstudents at SD Negeri 26 Arungkeke, Kabupaten Jeneponto. The type of this study was quasi experimental research. The design of this study was a non-quivalent control group design. This study found that the average score of students’ ability to write narrative essays in the control class for pretest was 63.90 and the average score for posttest was 74.52. Meanwhile, the average score of pretest in the experimental class was 59.48 and the average postest score was 80.24. The result of N-Gian score test in the control class was an average of 0.24152, indicating that the learning outcomes of writing narrative essays were low. Whereas, the average score of N-Gain test in the experimental class was 0.4640, indicating that the learning outcomes of writing narrative essays were moderate. After that, the result of T test revealed that tcount 2,283> ttable 0.021 so that Ho was rejected and Ha was received. The significant value of 2-tiled was 0.030 <sig. 0.05; thus, conferencing approach assisted by audio-visual media gave a significant effect on the students’ ability to write narrative essays at grade V SD Negeri 26 Arungkeke, Kabupaten Jeneponto.